2007
DOI: 10.1002/jts.20209
|View full text |Cite
|
Sign up to set email alerts
|

PTSD symptoms, substance use, and vipassana meditation among incarcerated individuals

Abstract: The present study evaluated whether Posttraumatic Stress Disorder (PTSD) symptom severity was associated with participation and treatment outcomes comparing a Vipassana meditation course to treatment as usual in an incarcerated sample. This study utilizes secondary data. The original study demonstrated that Vipassana meditation is associated with reductions in substance use. The present study found that PTSD symptom severity did not differ significantly between those who did and did not volunteer to take the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 46 publications
4
63
0
1
Order By: Relevance
“…[54][55][56][57][58]61,64 The remaining studies reviewed the efficacy of interventions based on mindfulness-based interventions, including yoga, meditation, and guided imagery. 51,59,60,62,[64][65][66][67][68][69][70] The studies reviewed here used mindfulness-based interventions in a wide range of high-risk disadvantaged populations, including racial/ethnic minorities, individuals with chronic health conditions (including AIDS and breast cancer), drug and alcohol users, and victims of interpersonal violence and trauma. All of the reviewed studies provided evidence that mindfulness-based interventions are effective in improving physical and mental health, functioning, self-care, and overall quality of life.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…[54][55][56][57][58]61,64 The remaining studies reviewed the efficacy of interventions based on mindfulness-based interventions, including yoga, meditation, and guided imagery. 51,59,60,62,[64][65][66][67][68][69][70] The studies reviewed here used mindfulness-based interventions in a wide range of high-risk disadvantaged populations, including racial/ethnic minorities, individuals with chronic health conditions (including AIDS and breast cancer), drug and alcohol users, and victims of interpersonal violence and trauma. All of the reviewed studies provided evidence that mindfulness-based interventions are effective in improving physical and mental health, functioning, self-care, and overall quality of life.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
“…Among incarcerated individuals, participation in mindfulness-based therapies was similarly associated with a reduction in mood disturbance and drug related behaviors. 51,53,70 The reviewed studies provide preliminary evidence of the feasibility and acceptability of mindfulness-based interventions among high-risk disadvantaged populations. The studies of MBSR among disadvantaged individuals reported program completion rates ranging from 66% to 70%, 57,61,64 which is slightly higher than retention rates that have been reported for other evidence-based mental health treatments.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
“…This measure was derived from an exploratory factor analysis of several previously developed mindfulness questionnaires (Baer, Smith, Hopkins, Krietemeyer, & Toney, 2006). The FFMQ is a five-factor, 39-item measure designed to assess mindfulness across five facets including observing, describing, acting with awareness, non-judging of inner experience and nonreactivity to inner experience (Simpson et al, 2007). Items are rated on a five-point scale ranging from 1 (never or very rarely true) to 5 (very often or always true).…”
Section: Assessment Of Mindfulnessmentioning
confidence: 99%
“…ESM is therefore ideally suited to investigate changes in people's emotional reactions to their daily environment (Csikszentmihalyi & Larson, 1987). To assess the extent to which mindfulness training increased the ability to focus attention, we chose to (Deng, Liu, Rodriguez, & Xia, 2011;Simpson et al, 2007). Furthermore, mediation analysis was used to test whether changes in inner peace were mediated by changes in mindfulness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation